SplicingCompass: differential splicing detection using RNA-Seq data - Aschoff, Moritz; Hotz-Wagenblatt, Agnes; Glatting, Karl-Heinz; Fischer, Matthias; Eils, Roland; König, Rainer (Bioinformatics, 2013)
Abstract. Motivation: Alternative splicing is central for cellular processes and substantially increases transcriptome and proteome diversity. Aberrant splicing events often have pathological consequences and are associated with various diseases and cancer types. The emergence of next-generation RNA sequencing (RNA-seq) provides an exciting new technology to analyse alternative splicing on a large scale. However, algorithms that enable the analysis of alternative splicing from short-read sequencing are not fully established yet and there are still no standard solutions available for a variety of data analysis tasks.
Gesehen am 26.10.2020